447. COVID-19 Prevalence Among COVID-19 Exposed Health Care Workers at a Tertiary Care Center in San Bernardino County, Ca. (31st December 2020) - Valenzuela, Kathleen Louise; Veltman, Jennifer; Wilson, April
Abstract: Background: We studied the prevalence of positive SARS-CoV2 antibody and positive SARS-CoV2 antigen among high risk health care workers at Loma Linda University Health System (LLUHS) who voluntarily obtained SARS-CoV2 antibody testing, and if indicated, antigen testing. The study determined that there is a significant decrease in the prevalence of SARS-CoV2 antigen among employees at LLUH compared to the community. Methods: Employee Health and Occupational Medicine offered antibody testing to employees who were considered high risk, primarily working in the Coronavirus Disease 19 (COVID-19) designated units. We tested 658 subjects' serum for the presence of IgM and IgG antibodies via the Nirmidas Qualitative SARS-CoV2 test. 29 subjects with a positive antibody test were subsequently tested for the presence of serum SARS-CoV2 antigen via PCR. Results: There were 31 subjects who tested positive for IgM or IgG antibodies. 11 subjects had positive IgM with negative IgG. 3 subjects had negative IgM with positive IgG. 15 patients had positive IgM and positive IgG. 2 subjects had positive IgM with negative IgG, were subsequently retested, and then found to have positive IgM and positive IgG. Of those 31 subjects with a positive antibody test, 2 were not tested for the COVID-19 antigen, 1 had an inconclusive test, 23 tested negative, and 5 tested positive. Of those 5 positive for the antigen, 2 had symptoms and 3 did not report symptoms or did not use the symptom questionnaire. The community prevalence of positive SARS-CoV2 antigen in San Bernardino is 0.37%, as of June 16. The prevalence of positive SARS-CoV2 antigen among LLUH employees is 0.03% and the prevalence of positive antibody is 0.18%. The value of z is -7.3206, p is < .00001. Thus, the result is significant at p < .01. Conclusion: The results of this testing supports the efficacy of the early protective measures that LLUHS implemented in preparation for the pandemic. Such protective measures include: mandated face masks, symptoms screening, testing for SARS-CoV2 antibody or antigen on patients admitted, a dedicated COVID-19 section of the emergency department as well as inpatient units, etc. Given the statistical significance of this study, the protective bundle can be used as a template for preventative measures for future pandemics. Disclosures: All Authors : No reported disclosures